Multi-channel dot-off-dot halftoning compensating for slightly chromatic gray inks - Gooran, Sasan; Zitinski Elias, Paula (Journal of Print and Media Technology Research, 2023)
Printing using more than four ink channels visually improves the reproduction but causes challenges with the ink layer thickness that could lead to ink bleeding and color inaccuracy. A color image is commonly prepared for print by first being separated into the colorant channels the intended print device utilizes. The separations are usually halftoned independently, resulting in random dot overlap with possible spots where all colorants are printed. A multilevel halftoning algorithm that processes each channel so that it is printed with multiple inks of the same hue value has already been applied to three achromatic inks – photo gray, gray, black – in a real paper–ink setup. Results proved a successful multilevel halftone implementation workflow using multiple inks while avoiding dot-on-dot placement. However, in this approach, the gray inks were assumed to be neutral and lighter versions of black, an assumption that may cause a ΔE*ab color difference as high as 5. In the present paper an alternative approach, based on dot-off-dot halftoning avoiding dot overlap, is proposed and applied to the same three inks. A look-up table driven separation procedure of the original image into the three channels is also proposed, which, combined with dot-off-dot halftoning, results in a ΔE*ab color difference not larger than 1.8. Results show that the dot-off-dot halftoned images are visually pleasant without any artifacts in tone transitions. The proposed approach has three main advantages to the commonly used independent halftoning. One being that dot overlap between different inks is completely avoided, i.e. photo gray, gray and black in the present work. The other one is that the results are less grainy compared to independent channel halftoning. The third one is that dot-off-dot halftoning consumes less ink than independent halftoning when reproducing the same color.